Healthy lifestyles and wellbeing reduce neuroinflammation and prevent neurodegenerative and psychiatric disorders - Kip, Elodie; Parr-Brownlie, Louise C. (Frontiers in Neuroscience, 2023)
Since the mid-20th century, Western societies have considered productivity and economic outcomes are more important than focusing on people’s health and wellbeing. This focus has created lifestyles with high stress levels, associated with overconsumption of unhealthy foods and little exercise, which negatively affect people’s lives, and subsequently lead to the development of pathologies, including neurodegenerative and psychiatric disorders. Prioritizing a healthy lifestyle to maintain wellbeing may slow the onset or reduce the severity of pathologies. It is a win-win for everyone; for societies and for individuals. A balanced lifestyle is increasingly being adopted globally, with many doctors encouraging meditation and prescribing non-pharmaceutical interventions to treat depression. In psychiatric and neurodegenerative disorders, the inflammatory response system of the brain (neuroinflammation) is activated. Many risks factors are now known to be linked to neuroinflammation such as stress, pollution, and a high saturated and trans fat diet. On the other hand, many studies have linked healthy habits and anti-inflammatory products with lower levels of neuroinflammation and a reduced risk of neurodegenerative and psychiatric disorders. Sharing risk and protective factors is critical so that individuals can make informed choices that promote positive aging throughout their lifespan. Most strategies to manage neurodegenerative diseases are palliative because neurodegeneration has been progressing silently for decades before symptoms appear. Here, we focus on preventing neurodegenerative diseases by adopting an integrated “healthy” lifestyle approach. This review summarizes the role of neuroinflammation on risk and protective factors of neurodegenerative and psychiatric disorders.